EXPLAINING DEMOCRATIC DECONSOLIDATION: EVIDENCE FROM ASIAN DEMOCRACIES - Saiful Mujani; R. William Liddle (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
Are Asian democracies deconsolidating, in line with world-wide trends? This article examines four consolidated democracies in Asia: Japan, South Korea, and Taiwan, plus Indonesia, whose own consolidation has been problematic. Using public opinion data, we evaluate two competing models—civic culture and political economy—to test whether there is a decline in democratic support. We report that the political economy model is more persuasive. Declines in democratic support are associated more consistently with democratic performance and education. Because education levels are tending to rise, and political socialization continues into adulthood, we conclude that there should be little fear that Asian democracies will deconsolidate.